Tale of a fish: quran stories for little hearts - Khan, Saniyasnain (GoodwordKidz New Delhi, 2004)
This story follows the journey of a fish that experiences various adventures in the sea, emphasizing themes of curiosity, bravery, and the importance of friendship. As the fish navigates challenges and learns valuable lessons along the way, it illustrates the significance of trust and support in overcoming difficulties, encouraging young readers to embrace exploration and kindness.